2011
DOI: 10.1159/000321955
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Colorectal Surgery in Patients with Prior Abdominal Surgery

Abstract: Purpose: We retrospectively investigated the impact of prior abdominal surgery on the outcome of laparoscopic colorectal surgery. Patients: Among 607 colorectal cancer patients who underwent laparoscopic surgery, 192 patients had previously undergone abdominal surgery (S group) and 415 had not (non-S group). Results: The percentage of female patients was higher in the S group than in the non-S group. The incidence of conversion to open surgery was higher in the S group (5.2%, 10/192) than in the non-S group (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…Despite the longer operating time and higher conversion rate, the mortality and morbidity and length of hospital stay were not significantly different in patients with and without PAOS. This is consistent with other reports (Table 5) [12,13,22,24–27].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Despite the longer operating time and higher conversion rate, the mortality and morbidity and length of hospital stay were not significantly different in patients with and without PAOS. This is consistent with other reports (Table 5) [12,13,22,24–27].…”
Section: Discussionsupporting
confidence: 94%
“…Two previous studies [12,26] have reported, as in the present study, a statistically higher conversion rate in patients with PAOS (Table 5). Furthermore, the conversion rate was higher in patients with PAOS in all other reports [13,22,24,25,27], although this did not reach statistical significance. These findings might be explained by the inclusion in the PAOS group of previous laparoscopic procedures and previous appendectomy by limited right lower‐quadrant incision, as Franko et al.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…A recent study suggested that only major previous GI surgery increases complication rates. 55 Fourth, because the data are derived purely from self-taught surgeons, the recommendations may not be applicable to all. Currently, many surgeons have already gained experience in LCS during their residency.…”
Section: Commentmentioning
confidence: 99%